2003
DOI: 10.1007/s00213-003-1429-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benzodiazepines on explicit memory in a paediatric surgery setting

Abstract: Overall, it appears that benzodiazepines do impair memory in a pediatric population. This amnesia was not secondary to the inattention and sedation also caused by midazolam administration. The theoretical and clinical implications of these findings are discussed, as are potential future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 37 publications
(55 reference statements)
5
31
2
Order By: Relevance
“…A number of studies have also suggested that benzodiazepines impair attention (Buffett-Jerrott et al 2003;Fleishaker et al 1995;Loke et al 1985;Rich et al 2006;Vidailhet et al 1994) which we also believe is implicated in the binding process (Diana and Reder 2006).…”
Section: What Do We Mean By "Binding"?mentioning
confidence: 63%
“…A number of studies have also suggested that benzodiazepines impair attention (Buffett-Jerrott et al 2003;Fleishaker et al 1995;Loke et al 1985;Rich et al 2006;Vidailhet et al 1994) which we also believe is implicated in the binding process (Diana and Reder 2006).…”
Section: What Do We Mean By "Binding"?mentioning
confidence: 63%
“…Ninety minutes before surgery, the researcher met with both the child and the parent(s) to obtain consent/ assent. The child's baseline level of sedation was then experimenter-rated using a five-point rating scale (Wilton et al 1988) used in previous studies of midazolam as a preoperative medicant in children (e.g., Buffett-Jerrott et al 2003;Wilton et al 1988). This scale has excellent inter-rater reliability (Buffett-Jerrott et al 2003).…”
Section: Pilot Testingmentioning
confidence: 99%
“…In addition, this study was designed to extend the Pringle et al results to younger children (aged 3-6 years) and to children undergoing surgery (i.e., myringotomy) rather than painful medical procedures. It was predicted that midazolam would impair explicit memory (hit rates on a visual recognition task) relative to placebo (cf., Buffett-Jerrott et al 2003;Kain et al 2000). In contrast, comparable implicit memory performance (i.e., priming level on a visual perceptual facilitation task) was expected among those in the midazolam and placebo groups.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…However, the acceptability of oral midazolam by pediatric patients is only 70%. Other undesirable effects including restlessness, paradoxical reaction, and negative postoperative behavioral changes have made it a less than ideal premedication (8,12) . Although amnesia is considered an advantage by some authorities, it has also been regarded as a possible disadvantage by others (15) .…”
Section: Introductionmentioning
confidence: 99%